Bivariate Analysis on Autism Therapy using Social Skills Training in SLB YPPA Padang - Ridhyalla Afnuhazi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Number of persons with autism in the world range of 60.000 - 150.000 autism occurred in children aged below 15 years. Therapy was given to improvement of social skills in autistic children Social Skills Training Therapy (SST). The purpose of this study was to determine the ability of Socialization Effects of SST for Autism Children (6 -12 years) in SLB Autism YPPA Padang 2015. Quasi - experimental design with one - group pre - post test. The population in this study all children with autism aged 6-12 year, and samples were taken by convenience sampling 30 people. Univariate date processing techniques while the frequency distribution and central tedensy and Bivariate date processing techniques with paired T - test. Results of research abilities children with autism after therapy SST, and light weight characteristic factors of symptoms associated with social skills of children with autism. Suggestions can be submitted to the study of nursing in order to detect early signs of the symptoms experienced by children with autism so there is no sign of severe symptoms and train the socialization skills of children with autism with SST therapy.